The book of Azrael - Nicole, Amber V. (Nicole, Amber. Gods & monsters series, 2025)
"World ender meets ender of worlds: A thousand years ago, Dianna gave up her life to save her dying sister. She called up anyone who would listen, not expecting a monster to answer. Now, she does what Kaden asks. Even if that means securing an ancient relic from the very creatures who hunt her. A king believed long dead: In the old world, his name was Samkiel. In the new world, it is Liam. But one title remains: world ender. A myth to his enemies, a savior and king to those loyal to him. After the gods war, he locked himself away. Hiding from the world, leaving the ones who needed him most to deal with the fallout"--Book jacket.